Protein sparing effect of a fermentation product in pig diets from weaning to market - Swanson, J.A.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred eighty pigs (avg wt of 21.11b) were used in an experiment to determine if a fermentation product improves performance and reduces last rib fat thickness in pigs when added to a low-protein diet regimen. Treatments were: 1) positive control (19-16-14% crude protein regimen during the nursery-growing-finishing phases); 2) positive control plus 2.50 lb/ton fermentation product; 3) low-protein regimen (17-14-12% crude protein during the nursery-growing-finishing phases); 4) low-protein regimen plus 1.25 lb/ton fermentation product; 5) low-protein regimen plus 2.50 lb/ton fermentation product; and 6) low-protein regimen plus 5.00 lb/ton fermentation product. As addition of fermentation product was increased from 0 to 5.00lb/ton in the low-protein regimen, average daily feed intake (ADFI) of nursery pigs decreased linearly. However, average daily gain (ADG) and feed to gain ratio (F/G) tended to be best for pigs fed 1.25 lb/ton of fermentation product compared to other treatments. During the growing and finishing phases, feeding the low-protein regimen reduced performance compared to the positive control. Compared to pigs fed the positive control, feeding 2.50 lb/ton of fermentation product tended to decrease ADFI and ADG but improved F/G. Feeding 2.50 and 5.00 lb/ton fermentation product reduced ADG and ADFI, and worsened F/G for pigs fed the low-protein regimen. Overall (from 21 to 220 lb), feeding the fermentation product at more than 1.25 lb/ton in the low-protein diet regimen tended to reduce performance, and pigs fed the low protein diets with or without the fermentation product had poorer performance (ADG, ADFI, F/G, and last rib fat thickness) than pigs fed the 19-16-14% crude protein diets.
Keywords: Swine; Starter; GF; Performance; Probiotic; Carcass; Additive